Legal Analysis of the OJK's Role in Rejecting Insurance Policy Claims by Customers - Sepia Walandari; Sinvani Dinda Sitepu; Daffa Akmal Manurung; Bagus Herlambang; Annisa Octavia (ISNU Nine-Star Multidisciplinary Journal, 2025)
Insurance is an institution that functions to mitigate various risks that may occur in the future. Therefore, insurance plays a crucial role in providing protection to policyholders. One of the challenges that frequently arise in insurance practice is the rejection of claims submitted by customers to insurance companies, which are usually accompanied by various reasons from the company. In this case, the existence of the Financial Services Authority (OJK) is very helpful for customers in resolving issues related to claim rejections. Based on Law Number 21 of 2011 concerning the Financial Services Authority, this institution not only serves as a facilitator of consumer protection and mediation, but also plays an active role in legal defense for customers. The OJK's role in resolving disputes over insurance claims rejected by insurance companies includes acting as a mediator in the deliberation process to reach a consensus between the customer and the insurance company, as well as acting as a supervisor to ensure the outcome of the agreement. However, in carrying out its functions, the OJK faces a number of non-legal obstacles, both internal and external. This research uses literature review and legal analysis to help provide results in addressing this issue. Some of these obstacles include the lack of clarity in customer complaints, incomplete supporting documents, and minimal information that can be obtained.